Panama Canal Meteorological Data_Vistamares - Steven Paton; Panama Canal Authority (Smithsonian Tropical Research Institute, 2021)
Data from the Panama Canal Authority (ACP) Vistamares meteorological station.
Most ACP meteorological stations provide the following parameters: air temperature, wind speed and direction, dew point, relative humidity, air pressure, solar radiation. Some stations, for some years (depending on what parameters the ACP made available that year) include interval max/min values, in addition to the interval average values.
Data have been freely provided by the Panama Canal Authority and are in the public domain.
Any publication using these data should credit the Panama Canal Authority.
Most data have been curated by STRI's Physical Monitoring Program.
All data are provided on an 'as is' basis.
Keywords: 50206 Environmental Monitoring; 40107 Meteorology